2015
DOI: 10.4238/2015.june.29.16
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical value of the soluble major histocompatibility complex class I-related chain A molecule in the serum of patients with renal tumors

et al.

Abstract: ABSTRACT. We investigated the expression and clinical value of the soluble major histocompatibility complex class I-related chain A (sMICA) molecule in the serum of patients with renal tumors. Sixty patients diagnosed with renal tumors were enrolled in the experimental group, whereas 20 healthy volunteers served as the control group. The sMICA levels were measured via enzyme-linked immunosorbent assay, and the results were analyzed in combination with data from pathology examination. The experimental group had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…High levels of circulating soluble MIC have been associated with poor clinical prognosis and metastasis in multiple cancer types, such as breast, colorectal, ovarian, prostate, lung and other cancers [13,4547]. Shedding of other family of NKG2D ligands, such as ULBP2 has also been reported to correlate with poor prognosis in selected cancer of solid tumors and hematological malignancies [4852].…”
Section: Nkg2d Ligands In Human Cancermentioning
confidence: 99%
“…High levels of circulating soluble MIC have been associated with poor clinical prognosis and metastasis in multiple cancer types, such as breast, colorectal, ovarian, prostate, lung and other cancers [13,4547]. Shedding of other family of NKG2D ligands, such as ULBP2 has also been reported to correlate with poor prognosis in selected cancer of solid tumors and hematological malignancies [4852].…”
Section: Nkg2d Ligands In Human Cancermentioning
confidence: 99%
“…It has been widely reported that low cell surface expression of MICA/B or elevated sera levels of soluble MICA and MICB correlate with metastasis in different types of cancer [67,68,69,70,71,72,73,74]. Elevated sera levels of soluble ULBP2 are an indicator of progression in melanoma patients [75].…”
Section: Metastasis and Evasion Of Nk Cell Surveillancementioning
confidence: 99%
“…On the other hand, the MICA and MICB have been described as generally highly polymorphic genes . Associations of these polymorphisms with different types of human diseases indicate their functional importance . MR1 polymorphisms are associated with the development of tuberculosis in humans, while MICA/B genetic variation is associated with viral as well as bacterial disease .…”
Section: Introductionmentioning
confidence: 99%
“…22 Associations of these polymorphisms with different types of human diseases indicate their functional importance. [23][24][25][26] MR1 polymorphisms are associated with the development of tuberculosis in humans, 27 while MICA/B genetic variation is associated with viral as well as bacterial disease. 28,29 For all these reasons, MHC class I and MHC class I-related molecules are of interest for biomedical research.…”
mentioning
confidence: 99%